Microglia Polarization from M1 toward M2 Phenotype Is Promoted by Astragalus Polysaccharides Mediated through Inhibition of miR-155 in Experimental Autoimmune Encephalomyelitis. (24th December 2021) - Liu, Xiaojun; Ma, Jinyun; Ding, Guiqing; Gong, Qianyi; Wang, Yuanhua; Yu, Hua; Cheng, Xiaodong
Abstract : Activated microglia is considered to be major mediators of the neuroinflammatory environment in demyelinating diseases of the central nervous system (CNS). Activated microglia are mainly polarized into M1 type, which plays a role in promoting inflammation and demyelinating. However, the proportion of microglia polarized into M2 type is relatively low, which cannot fully play the role of anti-inflammatory and resistance to demyelinating. Our previous study found that Astragalus polysaccharide s (APS) has an immunomodulatory effect and can inhibit neuroinflammation and demyelination in experimental autoimmune encephalomyelitis (EAE), which is a classic animal model of CNS demyelinating disease. In this study, we found that APS was effective in treating EAE mice. It restored microglia balance by inhibiting the polarization of microglia to M1-like phenotype and promoting the polarization of microglia to M2-like phenotype in vivo and in vitro . miR-155 is a key factor in regulating microglia polarization. We found that APS could inhibit the expression level of miR-155 in vivo and in vitro . Furthermore, we performed transfection overexpression and blocking experiments. The results showed that miR-155 mediated the polarization of microglia M1/M2 phenotype, while the selective inhibitor of miR-155 attenuated the inhibition of APS on microglia M1 phenotype and eliminated the promotion of APS on microglia M2 phenotype. Microglia can secrete IL-1 α, TNF- α, and C1q after polarizing into M1 type and induce the activation of A1 neurotoxic astrocytes, further aggravating neuroinflammation and demyelination. APS reduced the secretion of IL-1 α, TNF- α, and C1q by activated microglia, thus inhibited the formation of A1 neurotoxic astrocytes. In summary, our study suggests that APS regulates the polarization of microglia from M1 to M2 phenotype by inhibiting the miR-155, reduces the secretion of inflammatory factors, and inhibits the activation of neurotoxic astrocytes, thus effectively treating EAE.